Taxonomic studies on the genus Sanicula (Apiaceae) from China (I): The identity of S. orthacantha var. pumila and S. pengshuiensis - Li, Hui-Min; Song, Chun-Feng (Phytotaxa, 2022)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Sanicula lamelligera (Apiaceae) is highly variable in character of basal leaves, branches of inflorescences, and character of fruits. We therefore accept some previous synonyms of this species, including S. ichangensis, S. lamelligera var. wakayamensis, S. orthacantha var. longispina, S. satsumana, and S. yunnanensis, and further reduce S. orthacantha var. pumila, and S. pengshuiensis to its synonymy. Lectotypification is proposed for S. lamelligera var. wakayamensis and S. orthacantha var. pumila.